Changes in college students’ health behaviors and substance use after a brief wellness intervention during COVID-19 - Pfledderer, Christopher D.; Bai, Yang; Brusseau, Timothy A.; Burns, Ryan D.; King Jensen, Jessica L. (Preventive medicine reports, 2022)
College students exhibit low levels of physical activity, high levels of sedentary behavior, poor dietary behaviors, sleep problems, high stress, and increased substance use. On-campus resources offering programs to improve college students’ health have been limited during the pandemic. The purpose of this study was to test a brief intervention to improve multiple health behaviors among United States college students. The intervention was a single arm repeated measures study conducted over 12 weeks, utilizing the Behavior Image Model. The intervention involved three components: a survey, a 25-minute wellness specialist consult with a peer health coach, and a 15-minute goal planning session. Follow-up measures were completed at 2-, 6-, and 12-weeks post session to assess changes in wellness behaviors. Linear mixed effects models for repeated measures were used to analyze the association between intervention implementation on within-subject changes in physical activity, sedentary behavior, diet, general health, emotional wellness, and substance use. A total of 121 participants enrolled in the study and 90 (74.4%) completed the health coach session (71% female). At first follow-up, statistically significant increases were observed in vigorous physical activity days/week (coef. = 0.5,95%CI: 0.2,0.9), moderate physical activity days/week (coef. = 0.7, 95%CI: 0.2,1.1), general health (coef. = 4.8,95%CI: 2.1, 7.5), and emotional wellness (coef. = 8.6,95%CI: 5.8, 11.3). Statistically significant decreases in cannabis use (coef. = -2.3,95%CI:-4.1, −0.5) and alcohol consumption (coef. = -2.5,95%CI: −3.7,-1.3) were observed. Many of these changes were sustained at second and third follow-up. This brief wellness intervention shows promise to positively influence multiple health behaviors in college students.